Design and Fabrication of Drive Train System for Bosch Power Tools Cordless Race 2011 - Mohamad Mohaimin bin Mokhlis, Mohamad Mohaimin (Universiti Teknologi Petronas, 2011)
Drive train system is a system to transmit power from one or multiple energy source to one or multiple output. It is an important component in vehicle to provide the driving power to move the vehicle. Drive train can be powered by an engine or motor. In this project, a drive train system is required to be designed and fabricate using BOSCH power tools as the power source for an international competition. The project aims to design a reliable drive train system that use power tools as power source that is fabricated according to design and calculation done. The system design is required to meet the regulation uphold for the competition. The finished drive train is test by accelerating the kart to maximum possible speed in a test track, which is decided at Village 4’s parking lot, Universiti Teknologi PETRONAS. From the testing done, the system able to achieved top speed of 36km/h average. The speed is sufficient and reliable for the competition race track. At the end of the project, the drive train is proven to provide reliable output for the operation